The Origin and Development of English Novel: A Descriptive Literature Review - Choeda, Choeda (International Journal of English Literature and Social Sciences (IJELS), 2019)
Novel as a literary genre enjoyed the highest level of glory in the 18th century. The authors namely Defoe, Richardson, Fielding and Sterne contributed significantly to the development of English novel. They influenced the writers who came after them. The 18th century coincided with the industrial revolution which significantly contributed to the rise of the novel (with the invention of printing machine). The chain effects of industrial revolution improved people’s life and living standard. The rise of the educated middle class people further increased the reading public which correspondingly led to demand of novels for reading. Books such as ‘Don Quixote’, ‘Decameron’, ‘Morte d’ Arthur’ and ‘Pilgrim’s Progress’ laid the foundations for the development of the novel. ‘Pamela’, ‘Joseph Andrew’s, ‘Tristram Shandy’, and ‘Robinson Crusoe’ were some of the notable books that became famous in the 18th century. However, novels continued to evolve in the 19th and 20th century giving rise to different genres or classes of novel.